Efektivitas Relaksasi Aromaterapi terhadap Penurunan Tingkat Kecemasan Menghadapi Ujian pada Siswa Kelas VIII - Aisyah, Atika Surya; Widyastuti, Widyastuti; Siswanti, Dian Novita (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2024)
Test anxiety is a pervasive problem related to the evaluative of educational programs. It is necessary to learn about the nature, causes, effects, and treatment so it is important to give the interventions to reduce test anxiety the students can show their best performance. The purpose of this study was to determine the effectiveness of aromatherapy to students who will take the exam. The participants were 17 students of 8th Grade. This experimental research design is a time series control group design with a pre-test and post-test group models. A scale of Test Anxiety based on the aspects by Cassady and Johnson (2002) was used to measure anxiety levels with a reliability value of 0.944. The analytical method used is the Friedman and Kruskal-Wallis test. This study found that aromatherapy was effective in reducing calculations in the test using the Kruskal-Wallis test with the Asymp value.Sig p <0.05, the test scores for participants between group KK, KE1, and KE2 based on the pre-test results with p = 0.450 , post-test 1 with p = 0.025, post-test 2 with p = 0.019, and post-test 3 with p = 0.011. Aromatherapy can be used to reduce test anxiety as an effective independent therapy.